The Phenomenon Of Electronic Blackmail And Its Relationship To Suicide - Akbar, Ameer Ali; Ali Khalil, Zahraa; Mohsen, Ayat Sabah (Research Parks Publishers, 2024)
This study explores the significant relationships between various aspects of electronic blackmail and its impact on suicide, specifically in Iraq and the Arab world. Data presented in the study's tables reveal that: (1) Electronic blackmail targeting females in Iraq is significantly related to pressure from the blackmailer leading to the victim's suicide; (2) Electronic blackmail is one of the motives for suicide, and suicide often results from the pressure exerted by the blackmailer; (3) Excessive trust in online friends and weak family control contribute to blackmail, which can lead to suicide; (4) The blackmailer's electronic pressure is closely related to the victim's suicide; (5) Easy access to personal data is a key factor in blackmail, and electronic blackmail is a widespread phenomenon in Iraq and the Arab world. Based on these findings, the study recommends: (1) Strengthening family supervision; (2) Providing talk shows focused on blackmail; (3) Avoiding the sharing of personal photos with unknown individuals on social media; (4) Offering continuous information about cybercrimes and dealing with them transparently; (5) Implementing legislation to combat cybercrime through digital media; and (6) Promoting social security awareness through advertisements.